Dysfunction of Optineurin in Amyotrophic Lateral Sclerosis and Glaucoma - Toth, Reka P.; Atkin, Julie D. (Frontiers in Immunology, 2018)
Neurodegenerative disorders including amyotrophic lateral sclerosis (ALS), frontotemporal dementia, and glaucoma affect millions of people worldwide. ALS is caused by the loss of motor neurons in the spinal cord, brainstem and brain, and genetic mutations are responsible for 10% of all ALS cases. Glaucoma is characterized by the loss of retinal ganglion cells and is the most common cause of irreversible blindness. Interestingly, mutations in OPTN, encoding optineurin, are both associated with ALS and glaucoma. Optineurin is a highly abundant protein involved in a wide range of cellular processes, including inflammatory responses, autophagy, Golgi maintenance, and vesicular transport. In this review, we summarise the role of optineurin in cellular mechanisms implicated in neurodegenerative disorders, including neuroinflammation, autophagy and vesicular trafficking, focusing particularly on the consequences of expression of the mutations associated with ALS and glaucoma. This review showcases the impact of optineurin dysfunction in ALS and glaucoma.